COMPARATIVEANALYSIS OF MORPHOLOGICAL FEATURESOF HUMAN CLAVICLEAND STERNUM FORFORENSICANTHROPOLOGICAL PURPOSES (Journal of Forensic Medicine & Toxicology, 2018)
Identification of badly damaged human skeletal remains poses a serious challenge to forensic anthropologists. The non-metric osteological and mitochondrial DNA analyses are the preferred options for establishing the identity of such remains; the former  technique being comparatively simpler, easier, quicker and cheaper one. Present study was conducted with an  aim to investigate the comparative suitability of non- metric traits of clavicle and sternum for forensic anthropological purposes. Ten clavicular and eight sternal non-metric traits were examined for their sex and age dependency in 343 pairs of clavicles and equal number of sternums collected from Northwest Indian autopsied  cadavers. Significant sex and age dependent variations were noticed in almost all the clavicular features except conoid and deltoid tubercles. Male clavicles were either ‘long and smooth’ or ‘long and robust’ whereas the females  had mostly ‘short and smooth’ clavicles. Indian clavicles show epiphyseal union activity for later years than most other nationalities. The arch-shaped ventral prominence on manubrium, crescent costal incisures, mesosternal  ventral strips etc., were found the male sternal characteristics. The clavicular non-metric traits had higher forensic anthropological significance than the sternal features.
Keywords: Forensic anthropology; non-metric traits; clavicle and sternum; age and sex estimations; comparative analysis